Early-life mental disorders and adult household income in the World Mental Health Surveys - Kawakami, Norito (2012)
BACKGROUND: Better information on the human capital costs of early-onset mental disorders could increase sensitivity of policy-makers to the value of expanding initiatives for early detection-treatment. Data are presented on one important aspect of these costs: the associations of early-onset mental disorders with adult household income. METHODS: Data come from the WHO World Mental Health (WMH) Surveys in eleven high income, five upper-middle income, and six low/lower-middle income countries. Information about 15 lifetime DSM-IV mental disorders as of age of completing education, retrospectively assessed with the WHO Composite International Diagnostic Interview, was used to predict current household income among respondents ages 18-64 (n = 37,741) controlling for level of education. Gross associations were decomposed to evaluate mediating effects through major components of household income. RESULTS: Early-onset mental disorders are associated with significantly reduced household income in high and upper-middle income countries but not low/lower-middle income countries, with associations consistently stronger among women than men. Total associations are largely due to low personal earnings (increased unemployment, decreased earnings among the employed) and spouse earnings (decreased probabilities of marriage and, if married, spouse employment and low earnings of employed spouses). Individual-level effect sizes are equivalent to 16-33% of median within-country household income, while population-level effect sizes are in the range 1.0-1.4% of Gross Household Income. CONCLUSIONS: Early mental disorders are associated with substantial decrements in income net of education at both individual and societal levels. Policy-makers should take these associations into consideration in making healthcare research and treatment resource allocation decisions.